Regions of discrimination: felony records, race, and expressed college admissions policies - Evans, Douglas N. (Journal of crime and justice, 2023)
Criminal records can have consequences for higher education attainment despite the benefits of college degrees for formerly incarcerated people. Using stratified random sampling of colleges and universities across the 50 states, this study examines how higher education institutions claim to use felony history in admission decisions, and the impact of race, geography, and institutional factors associated with these decisions. Findings indicate that admissions departments are more likely to tell an interested applicant with a stereotypical Black name and a non-violent felony record that their criminal histories will be considered in the application process compared to another prospective applicant with a stereotypical White name and non-violent felony record. Admissions departments in public institutions and institutions with higher racial diversity are less likely to consider felony history. Lastly, institutions in the former Confederate states are more likely to indicate using stringent reviews of applicants who disclose a felony compared to institutions in the former Union states. Institutions in the former border states and unincorporated states claim to be less likely to consider criminal history in the applicant review process compared to Union states. Recommendations for addressing these barriers to higher education are presented.